Complementary Effect of Maternal Sildenafil and Fetal Tracheal Occlusion Improves Lung Development in the Rabbit Model of Congenital Diaphragmatic Hernia. Issue 3 (March 2022) - Russo, Francesca Maria; Da Cunha, Marina Gabriela Monteiro Carvalho Mori; Jimenez, Julio; Lesage, Flore; Eastwood, Mary Patrice; Toelen, Jaan; Deprest, Jan
Abstract : Objective: To evaluate the effect of combining antenatal sildenafil with fetal tracheal occlusion (TO) in fetal rabbits with surgically induced congenital diaphragmatic hernia (CDH). Background: Although antenatal sildenafil administration rescues vascular abnormalities in lungs of fetal rabbits with CDH, it only partially improves airway morphometry. We hypothesized that we could additionally stimulate lung growth by combining this medical treatment with fetal TO. Methods: CDH was created on gestational day (GD)23 (n=54). Does were randomized to receive either sildenafil 10 mg/kg/d or placebo by subcutaneous injection from GD24 to GD30. On GD28, fetuses were randomly assigned to TO or sham neck dissection. At term (GD30) fetuses were delivered, ventilated, and finally harvested for histological and molecular analyses. Unoperated littermates served as controls. Results: The lung-to-body-weight ratio was significantly reduced in sham-CDH fetuses either (1.2 ± 0.3% vs 2.3 ± 0.3% in controls, P =0.0003). Sildenafil had no effect on this parameter, while CDH fetuses undergoing TO had a lung-to-body-weight ratio comparable to that of controls (2.5 ± 0.8%, P <0.0001). Sildenafil alone induced an improvement in the mean terminal bronchiolar density (2.5 ± 0.8 br/mm 2 vs 3.5 ± 0.9 br/mm 2, P =0.043) and lung mechanics (static elastance 61 ± 36 cmH2 O /mL vs 113 ± 40 cmH2 O/mL, P =0.008), but both effects were more pronounced in fetuses undergoing additional TO (2.1 ± 0.8 br/mm 2, P =0.001 and 31 ± 9 cmH2 O/mL, P <0.0001 respectively). Both CDH-sham and CDH-TO fetuses treated with placebo had an increased medial wall thickness of peripheral pulmonary vessels (41.9 ± 2.9% and 41.8 ± 3.2%, vs 24.0 ± 2.9% in controls, P <0.0001). CDH fetuses treated with sildenafil, either with or without TO, had a medial thickness in the normal range (29.4% ± 2.6%). Finally, TO reduced gene expression of vascular endothelial growth factor and surfactant protein A and B, but this effect was counteracted by sildenafil. Conclusion: In the rabbit model for CDH, the combination of maternal sildenafil and TO has a complementary effect on vascular and parenchymal lung development. Abstract : Supplemental Digital Content is available in the text